Dynamical responses and analysis of rotor-nacelle systems subjected to aerodynamic and base excitations - Quintana, A.; Saunders, B. E.; Vasconcellos, R. [UNESP]; Abdelkefi, A. (Springer Nature, 2024)
The whirl flutter in rotor-driven aircraft is a significant aeroelastic instability resulting from the intricate interplay between structural, gyroscopic, and aerodynamic effects, exacerbated by nonlinearities. This phenomenon manifests as oscillatory behaviors within the aircraft's structure, carrying the risk of severe consequences and potential hazards. In this research endeavor, a nonlinear reduced-order model incorporating quasi-steady aerodynamics is employed to comprehensively analyze the behavior of a nacelle-rotor system and gain valuable insights into the dynamics of whirl flutter and its combined effect with external moments due to base excitations. Specifically, the study investigates the impact of external moment disturbances in conjunction with the aerodynamic excitations on the dynamical responses of a rotor-nacelle system, using parameters of a simplified model from previous studies as a basis for analysis. This investigation utilizes a solution methodology that includes linear and nonlinear approaches in order to explore the influences of rotor angular velocity, blade length, the number of blades, and their interplay with external moments applied to pitch and yaw degrees of freedom. The findings demonstrate the importance of considering these factors concerning the concurrent oscillations due to whirl flutter and other external moments with regard to the potential for resonance, quenching, and nonlinear responses in the system’s dynamics.
Keywords: Dynamics; Nonlinear; Quenching phenomenon; Resonance; Rotor-nacelle systems; Whirl flutter